2019
DOI: 10.3390/bs9120130
|View full text |Cite
|
Sign up to set email alerts
|

Features of Media Multitasking in School-Age Children

Abstract: The paper addresses the phenomenon of media multitasking that is being widely spread among children and adolescents in the context of digital socialization. The previous research has revealed its strong connection with cognitive control, executive functions, and academic performance, yet the specificity and efficacy of media multitasking performance, especially among children while they carry out usual activities, remains insufficiently studied. A quasi-experimental study, including digital tasks of various ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 22 publications
3
2
0
Order By: Relevance
“…e results support ndings on the prevalence of multitasking strategy among the younger generation, using it to adapt to mixed reality (Colledani et al, 2023). Adolescents more o en choose "average" multitasking strategy, and the percentage of "heavy" multitaskers appears to be small, which is consistent with other studies (Soldatova et al, 2020a). In the current study, no di erences in performance were found between single-taskers, "average", and "heavy" multitaskers.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…e results support ndings on the prevalence of multitasking strategy among the younger generation, using it to adapt to mixed reality (Colledani et al, 2023). Adolescents more o en choose "average" multitasking strategy, and the percentage of "heavy" multitaskers appears to be small, which is consistent with other studies (Soldatova et al, 2020a). In the current study, no di erences in performance were found between single-taskers, "average", and "heavy" multitaskers.…”
Section: Discussionsupporting
confidence: 91%
“…For both children and adults, this format is seen as a new digital sociality that has emerged in response to the increased demands of the environment. Empirical data show that MMT is a common activity format among adolescents (May & Elder, 2018;Soldatova et al, 2020a), which is also penetrating education.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that about 12% of children used to be occasionally engaged in media multitasking. It was found that multitasking habits increase with age, which is consistent with the results of other studies (Gutnick et al, 2010; Kabali et al, 2015; Soldotova et al, 2019). A study conducted on seven to eleven years old children in Singapore demonstrated that the more actively the children use digital devices, the more they seem to have a higher level of multitasking (Soldotova et al, 2019).…”
Section: Discussionsupporting
confidence: 91%
“…It was found that multitasking habits increase with age, which is consistent with the results of other studies (Gutnick et al, 2010; Kabali et al, 2015; Soldotova et al, 2019). A study conducted on seven to eleven years old children in Singapore demonstrated that the more actively the children use digital devices, the more they seem to have a higher level of multitasking (Soldotova et al, 2019). Research on media multitasking is still in a nascent stage and there is a need to develop methodologies that can accurately track the multitasking habits of children to assess its impact on time management, social interaction and overall development of younger children (Gutnick et al, 2010; Kabali et al, 2015).…”
Section: Discussionsupporting
confidence: 91%